The expression of P2Y6 receptor promotes the quality of mucus in colitic mice. (25th March 2021) - Placet, Morgane; Molle, Caroline M.; Arguin, Guillaume; Geha, Sameh; Gendron, Fernand‐Pierre
Abstract : In the intestine, mucins are expressed and secreted by goblet cells and enterocytes in a constitutive manner and in response to secretagogues to form a protective mucus layer. This protective barrier is often lost in inflammatory bowel disease (IBD). Interestingly, extracellular nucleotides, through P2Y receptors, were identified as mucin secretagogues in mucinous epithelia. These nucleotides are found in the intestine's extracellular milieu under basal conditions and in higher concentrations in pathologies such as IBD. It was observed that the mucus layer was affected in P2ry6 knockout mice suffering from dextran sodium sulfate (DSS)‐induced colitis. P2ry6 −/− mice were more sensitive to DSS‐induced colitis, resulting in larger ulcers and increased disease activity index. Interestingly, the absence of P2Y6 receptor expression negatively affected the mucus quality, as shown by a reduction in sulfomucin staining and the absence of a dense internal fucosylated mucin layer in P2ry6 −/− mice. Hence, we cannot rule out that the absence of P2Y6 receptors in knockout animals could negatively impact mucin secretion. However, we did not measure a reduction in the number of goblet cells, as previously reported. Instead, the results suggest that goblet cells rapidly discharged mucins to compensate for the mucus layer's increased lability, which resulted in empty goblet cells that are less visible to mucin staining. This study's results, along with previous reports, point toward a protective role for the P2Y6 receptor in IBD. Abstract : The absence of P2Y6 receptor expression renders mice more sensitive to DSS‐induced colitis as displayed by larger ulcers, poor mucus quality, and the absence of the inner dense protective mucus layer.